Exact solution for a three-dimensional three-body problem with harmonic interactions - De Castro, Antonio S. [UNESP]; Sugaya, Marcelo F. [UNESP] (IOP Publishing, 1993)
The three-dimensional three-body problem with non-equal masses interacting through pairwise harmonic forces of non-equal strengths is analysed. It is shown that the Jacobi coordinates per se do not decouple this problem but lead to the problem of two coupled three-dimensional harmonic oscillators which becomes exactly soluble through the use of an additional coordinate set.